FAMILY INFLUENCE ON THE DEVELOPMENT OF CHILDREN - Erna Roostin (IKIP Siliwangi, 2018)
The family is a group of people or a group of people living in one household because of blood relations, marriage or other bonds, living together in a house headed by a family head and eating in a pot. They interact with each other, have their own roles and create and maintain a culture. The role of the family as the main educator in the family is claimed to work together to educate their children. The main role of the family in educating children is as a foundation for moral education and religious life. The nature and nature of children are largely derived from both parents and from other family members. Family environment is the first educational environment because in this family every individual or a child first get education and guidance. In providing education should pay attention to the development of children. The development of the child is a change in the child where the infinite development of the growing sense of growth, but in it also contains a series of changes that take place continuously and are fixed from the physical and spiritual functions of the individual to the stage of maturity through growth, maturation and learning , there are several periods of development that must be achieved by the child. Therefore the family has a very important influence in the period of child development in order to have a basic knowledge of the ethics and norms that prevail in the community against himself.